2013
DOI: 10.5376/ijms.2013.03.0027
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation of Pb, Cd, Cu, and Cr by <i>Porphyridium cruentum</i> (S.F. Gray) Nägeli

Abstract: The red microalgae Porphyridium cruentum (S.F. Gray) Nägeli usually was used as feeds, a pigment for food and cosmetic, and antiviral activity that might be became industrial interest. Similar to another microalgae, P. cruentum has an ability to remediate heavy metals pollution, however research on it still limited. This research was conducted in order to find out the accumulation of Pb, Cd, Cr, and Cu on the P. cruentum. A laboratory experiment were developed with different concentrations. Based on this resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 29 publications
0
14
0
1
Order By: Relevance
“…Porphridium cruentum is unicellular marine red micro algal (Rhodophyta) species (21). In P. cruentum, the presence of starch, carbohydrates and sugar monomers (glucose, xylose, methyl glucaronic acid) of polysaccharides makes it a potential carbon source (22) and the biomass consists of 32% (w/w) available carbohydrates and 34% (w/w) crude proteins (23). This showed that it could be a potent agent for removal of heavy metals.…”
Section: Introductionmentioning
confidence: 99%
“…Porphridium cruentum is unicellular marine red micro algal (Rhodophyta) species (21). In P. cruentum, the presence of starch, carbohydrates and sugar monomers (glucose, xylose, methyl glucaronic acid) of polysaccharides makes it a potential carbon source (22) and the biomass consists of 32% (w/w) available carbohydrates and 34% (w/w) crude proteins (23). This showed that it could be a potent agent for removal of heavy metals.…”
Section: Introductionmentioning
confidence: 99%
“…S. platensis tolerated to a high Pb 2+ concentration, therefore able to remediate contaminated waters [ 23 ]. Soeprobowati and Hariyati (2013) had shown that the population growth of Porphyridium cruentum was high in the concentration of 1 mg/L Pb 2+ , Cd 2+ , and Cu 2+ . In the concentration of 3 mg/L Pb 2+ , Cd 2+ , and Cu 2+ .…”
Section: Resultsmentioning
confidence: 99%
“…Phycoremediation is the process in which algae are used to clean up the environment from pollutant [ 7 ]. Soeprobowati and Hariyati (2013) tent to used the term of phycoremediation for the used of microalgae to remediate environmental pollution [ 8 ]. Biological methods such as biosorption or bioaccumulation promote an advantages to physico-chemical methods on reducing the contaminant from the industrial effluent [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Laju pertumbuhan yang sedikit merupakan ciri khas dari fase adaptasi (Gambar 1) Pertumbuhan yang sangat kecil dikarenakan mikroalga menyesuaikan diri pada lingkungan yang baru (Soeprobowati et al, 2013 (Olivares, 2003).…”
Section: Hasil Dan Pembahasanunclassified